Genetic Variation and Evolutionary Analysis of Eggplant Mottled Dwarf Virus Isolates from Spain - Alfaro-Fernández, Ana; Taengua, Rafael; Font-San-Ambrosio, Isabel; Sanahuja-Edo, Esmeralda; Peiró, Rosa; Galipienso, Luis; Rubio, Luis (MDPI, 2024)
The genetic variation and population structure of gene N (nucleocapsid) and part of gene L (replicase) from 13 eggplant mottle dwarf virus (EMDV) isolates from Spain were evaluated and compared with sequences of EMDV isolates from other countries retrieved from GenBank. Phylogenetic inference of part of gene L showed three main clades, one containing an EMDV isolate from Australia and the other two containing isolates from Iran and Europe, as well as four subclades. EMDV isolates from Spain were genetically very similar and grouped in a subclade together with one isolate from Germany and one from the UK. No new recombination events were detected in addition to one recombination previously reported, suggesting that recombination is rare for EMDV. The comparison of synonymous and non-synonymous rates showed that negative selection played an important role, and only two codons were under positive selection. Genetic differentiation (Fst test), phylogenetic and nucleotide diversity analyses suggest a unique introduction of EMDV to Spain and low gene flow with other countries. In contrast, Greece and Italy showed diverse populations with high gene flow between both.